Secondary Brain Injury by Oxidative Stress After Cerebral Hemorrhage: Recent Advances - Shao, Linqian; Chen, Sichao; Ma, Li (Frontiers in Cellular Neuroscience, 2022)
Intracerebral Hemorrhage (ICH) is a type of clinical syndrome in which blood accumulates in the brain parenchyma due to the non-traumatic rupture of blood vessels in the brain.Because of Intracerebral Hemorrhage’s high morbidity and mortality, and the search for a more effective cure has not gone far enough ,the researchers'interest has been aroused in the treatment of cerebral hemorrhage. Meanwhile, after intracerebral hemorrhage occurs, oxidative stress plays a key role in majority of the brain injury. This review will discuss the pathway and effect of oxidative stress after intracerebral hemorrhage and its relationship with inflammation and autophagy, and make an assay of the current anti-oxidative therapy for intracerebral hemorrhage, so as to find a preferable therapeutic method or target for cerebral hemorrhage.